Layer-dependent solvent vapor annealing on stacked ferroelectric P(VDF-TrFE) copolymers for highly efficient nanogenerator applications. (9th September 2020) - Jiang, Yi-Pei; Yang, Tzu-Chuan; Lin, Ting-Han; Ho, Ching-Mei; Chan, Shun-Hsiang; Wu, Ming-Chung; Wang, Jer-Chyi
Abstract: Layer-dependent solvent vapor annealing (LDSVA) treatment using dimethylformamide (DMF) vapor on specific layers of stacked poly(vinylidenefluoride-co-trifluoroethylene) (P(VDF-TrFE)) copolymers by metal-ferroelectric-metal (MFM) capacitors and nanogenerators was investigated in this study. Prior to the fabrication of the devices, X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM) were performed to analyze the polarization of the crystalline β-phase in LDSVA-treated stacked P(VDF-TrFE) copolymers. After the LDSVA treatment on the top and bottom of the stacked films, the ferroelectric properties of P(VDF-TrFE) MFM capacitors became asymmetric. This can be confirmed via the bias electric field ( E bias ) and non-switchable leakage current due to the non-uniform distribution of polarized dipoles. With an increase in LDSVA treatment time, the arrangement of polarized dipoles in stacked P(VDF-TrFE) copolymers was significantly enhanced, especially the samples with the treatment on the bottom of the stacked films, contributing to a large remnant polarization (2 P r ) and a low coercive electric field ( E c ) of the MFM capacitors. Additionally, the piezoelectric nanogenerators with LDSVA treatment on stacked P(VDF-TrFE) copolymers presented a large open-circuit output voltage of more than 4.02 V at 7 Hz under an applied force of 800 g, which is approximately 3 times larger than that of the samples without treatment. The LDSVA-treated stacked P(VDF-TrFE) copolymers with superior ferroelectric and nanogenerator behaviors exhibit good potential with regard to highly efficient energy harvesting applications. Graphical abstract: Image 1 Highlights: Layer-dependent solvent vapor annealing (LDSVA) is applied on stacked P(VDF-TrFE). LDSVA-treated P(VDF-TrFE) MFM capacitors with superior ferroelectricity are obtained. An asymmetric ferroelectricity is found due to non-uniformity of polarized dipoles. High-efficiency nanogenerators with an output voltage of 4.02 V at 7 Hz are achieved.